Panel Regression : Determinan Struktur Modal Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Farmasi Di Bursa Efek Indonesia - irawan irawan; Peberlisma Br Sitepu (CERED Indonesia Institute, 2021)
This study aims to prove the factors influencing capital structure and profitability mediation. The analytical method used in this study is a causal design method, with statistical analysis testing, panel data and path analysis. The sampling method used is purposive sampling with a total sample of 6 pharmaceutical companies listed on the Indonesia Stock Exchange and data from 2013 – 2019. The results of this study indicate that company size has a significant effect on profitability. Liquidity has a significant effect on profitability. Firm size and liquidity simultaneously have a significant effect on profitability. Firm size has no significant effect on capital structure. Liquidity has a significant effect on the capital structure. Profitability has no significant effect on capital structure. Firm size, liquidity and profitability simultaneously have a significant effect on capital structure. Profitability does not function as an intervening variable between firm size and capital structure. Profitability serves as an intervening variable between liquidity and capital structure..